The Relationship Between Blood Glucose Levels To The Results Mycobacterium Tuberculosis Examination In Tuberculosis Patients - Puspita, Ria; Suliati, Suliati; Mutiarawati, Diah Titik (Poltekkes Kemenkes Mataram, 2023)
Tuberculosis (TB) is still high. 10.4 million new cases of TB occur and 1.4 million die from the disease is found The World Health Organization (WHO). Elevated blood glucose can lead to more severe tuberculosis infection, reactivation of dormant tuberculosis foci, and poor treatment outcomes. Determine the relationship of blood glucose levels to the results of Mycobacterium tuberculosis examination in suspected tuberculosis patients in Ketapang Banyuwangi area is the purpose of this of research study. The method was correlational analytic design of this study. The results conducted on 118 people who performed tuberculosis screening examinations, 32 people who qualified as a population. And 30 (thirty) people who meet the inclusion requirements as research samples. The results of the patient's molecular rapid test showed 6 (six) people were positive (+), and the results of the patient's culture showed 3 (three) people were positive (+) and 3 (three) other people were negative (-). While the results of fasting blood glucose level examination in 3 (three) tuberculosis patients conducted periodically (every week) for 5 (five) weeks were in the range of 78mg/dL - 150mg/dL. The conclusion is that there is a significant relationship between blood glucose levels and results of Mycobacterium tuberculosis examination of tuberculosis patients in the first, second and third patients in Ketapang Banyuwangi area.